Fundamental Theory and Key Technology of Software Defined Cloud Data Center Network - Dan Li; Fangming Liu; Deke Guo; Yuan He; Xiaomeng Huang (Dianxin kexue)
The main research contents of the national basic research program of China（973 program）“Fundamental Theory and Key Technologies of Software Defined Cloud Data Center Network”was introduced.The challenges of cloud data center network faces currently were pointed out,and the solutions based on software defined networking were proposed.The four research tasks for software defined cloud data center network research were elaborated,namely,architecture of software defined cloud data center network,optimization of cloud data center network resource utilization,resource management of multi-tenant cloud data center network,and coordinated control of cloud data center network energy.